Effectiveness of a herbal mouthrinse on de novo plaque formation - R.S., Jippy; S.R., Ananda; Jain, Jithesh (International Journal of Dental Research, 2017)
Background: Herbal mouthrinses have been recently introduced with the objective of achieving effective plaque control. Till date, chlorhexidine has been a gold standard with regard to anti-plaque agents.Objectives: To compare the effeciveness of the herbal mouthrinse (Hiora) against chlorhexidine mouthrinse.Methods:The study is a randomized, double blind, crossover clinical study. At the baseline, the volunteers brush their teeth using toothpaste without any active ingredient for 2 minutes. Oral prophylaxis was performed to ensure that the teeth are free of plaque, stains and calculus. Each subject was randomly assigned to both the experimental groups. During the trials, the volunteers were rinsed their mouths, according to the assigned random sequence of treatments: Chlorhexidine as chemical and HiOra as herbal mouthrinse. Both the mouthrinses were packed in similar coloured bottles but labeled differently and randomly administered to the subjects by a blinded operator. Each subject received oral and written instructions on the use of mouth rinses. After one week, the study subjects were asked to suspend their oral hygiene for 24 hours, and accumulated plaque was re-evaluated with erythrosine. The plaque index was recorded in the six selected teeth at the end of the trial. After the trial period, the usual oral hygiene habits resumed.Results: There were no statistically significant differences between herbal and chemical mouthrinses.Conclusion: Herbal mouth rinses may be as effective as chlorhexidine as chemical anti-plaque agents with fewer side effects.